POSTMODERNISME DALAM KEARSIPAN: Array - Khoerun Nisa Fadillah (Jurnal Kearsipan, 2014)
This research aims to analyze and describe the postmodernism in the archives. This is a descriptive qualitative research. Data collection used was literature. The technique of data analysis used was inductive analysis technique. The result showed important conclusions, namely: postmodernism archival thinking considers: 1) archives as a process rather than a product and shaping rather than documenting; 2) archival work on how represent the reality rather than keep the evidential accountability and how construct the nation collective memory rather than guard the government collective memory; 3) archivists as auditors rather than keepers and as constructors rather than guardians.